ANALISIS YURIDIS PERUBAHAN KONTRAK TERINTEGRASI MULTIYEARS PEMBANGUNAN JALAN DAN JEMBATAN DALAM PERSPEKTIF HUKUM KEPERDATAAN - Jamanna Sembiring; Markoni Markoni; I Made Kantikha; Joko Widarto; Tuti Elawati (Smart Education, 2026)
Abstract: This study analyzes contractual amendments within multiyears integrated con-struction contracts. Such contracts are generally complex and urgent in nature, requiring both the design and implementation phases to be carried out by a single provider, with the contract duration exceeding 12 months. The issues examined concern the legal certainty of contract amendments and the potential legal implications arising from changes to con-tractual clauses in integrated contracts after the completion of the contract period. This research employs a normative legal research method using statutory, conceptual, and case-based approaches. The findings indicate that eleven contractual amendments were made, which should have met the validity requirements of agreements under Article 1320 of the Indonesian Civil Code. Several issues were identified: deficiencies in the legal ca-pacity of the parties signing the amendments, changes to the contract implementation pe-riod that overlooked conditions related to SCM implementation failures, modifications to performance measurement and payment mechanisms that undermined legal certainty, and alterations to project deliverables during contract termination that failed to comply with the specific legal norms governing public procurement. The study results that the amend-ment processes undertaken create potential legal issues concerning the validity of the agreement and the assurance of legal certainty in fulfilling the parties’ rights and obliga-tions. Keywords: Contract Amendment, Integrated Contract, Multiyears. Abstrak: Penelitian ini menganalisis perubahan kontrak konstruksi terintegrasi multi-years. Kontrak konstruksi terintegrasi multiyears umumnya memiliki sifatnya komplek dan mendesak sehingga perancangan dan pelaksanaan dilakukan satu penyedia dengan pelaksanaan kontrak lebih dari 12 bulan. Permasalahan yang dikaji adalah kepastian hukum perubahan kontrak dan potensi dampak hukum perubahan klasul kontrak terin-tegrasi pasca masa pelaksanaan kontrak berakhir. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan pendekatan kasus. Hasil penelitian menunjukkan bahwa telah dilakukan 11 kali peru-bahan kontrak yang seharusnya memenuhi syarat sahnya perjanjian Pasal 1320 KUHPerdata. Dalam hal perubahan para pihak penandantangan kontrak memiliki kelemahan kecakapan, perubahan waktu pelaksanaan kontrak mengabaikan kondisi keg-agalan pelaksanaan SCM, perubahan pengukuran prestasi dan pembayaran pekerjaan yang tidak mendukung kepastian hukum atas sesuatu hal, dan perubahan keluaran da-lam pengakhiran kontrak yang mengabaikan norma-norma leg spesialis pengadaan ba-rang/jasa pemerintah. Hasil penelitian menunjukkan bahwa proses perubahan yang dil-akukan menimbulkan potensi permasalahan hukum atas kebasahan perjanjian dan kepastian hukum dalam pemenuhan hak dan kewajiban. Kata kunci: Kontrak Terintegrasi, Multiyears, Perubahan Kontrak.